Off-shell effects in electromagnetic interaction with bound nucleons - Belyaev, A.A.; Glöckle, W.; Golak, J.; Kamada, H.; Kotlyar, V.V.; Witała, H. (Вопросы атомной науки и техники, 2001)
Off-energy-shell effects in one- and two-nucleon photoabsorption are studied in the reaction γ³He → pd at intermediate energies. The calculations are carried out with the ³He wave functions for the Bonn and Paris potentials.